Nongenetic control of receptor signaling dynamics using a DNA-based optochemical tool. Issue 48 (24th May 2021) - Ueki, Ryosuke; Hayashi, Shota; Tsunoda, Masaya; Akiyama, Momoko; Liu, Hanrui; Ueno, Tasuku; Urano, Yasuteru; Sando, Shinsuke
Abstract : We demonstrated the nongenetic temporal control of cell signaling using a DNA-based synthetic surrogate of growth factor. Abstract : Optochemical tools that can modulate the activity of the target protein provide an opportunity for studying and regulating the related biological processes. Here we present a DNA-based nongenetic optochemical tool that can control the dynamics of growth factor signaling. This photo-caged mimicry of growth factor can be a promising tool for elucidating a linkage between the dynamics of signaling and the resulting biological outcomes, as well as for manipulating cellular functions and the fate of living cells.